Circuitos camponses: condições para a persistência do campesinato - Pedro de Carvalho Costa (2022)
This research proposed to study the circuits created, animated, maintained and reproduced by the peasantry and its way of life in the context of the 21st century. The research starts from the assumption that the peasantry has been resignified in the secular and continuous process of persistence, a phenomenon called repeasantization. First, the research effort was directed towards the identification of the mechanism logic of the peasantry — of production and circulation —, based on three interconnected and complementary pillars: a) family labor; 2) management of agroecosystems; 3) the search for autonomy. The research unfolded as it deepening of the operational means of these pillars, emphasizing the role of co-production with nature, and identifying the importance of co-production with the community in the process of (re)existence, (re)production and maintenance of peasant circuits. Empirical research was carried out on circuits in the RMBH and Vale do Jequitinhonha, enabling practical analyzes of the topic addressed. It was identified that co-production — with nature and with the community — and its intensification are fundamental factors for making the repeasantization process viable.